tìm y biết:
y-1/2-1/6-1/12-1/20-1/30-1/42=1
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(y-\frac{1}{2}-\frac{1}{6}-\frac{1}{12}-\frac{1}{20}-\frac{1}{30}-\frac{1}{42}=1\)
\(y-\frac{210}{420}-\frac{70}{420}-\frac{35}{420}-\frac{21}{420}-\frac{14}{430}-\frac{10}{420}=1\)
\(y-\frac{210-70-35-21-14-10}{420}=1\)
\(y-\frac{60}{420}=1\)
\(y-\frac{1}{7}=1\)
\(y=1+\frac{1}{7}\)
\(y=\frac{7}{7}+\frac{1}{7}\)
\(y=\frac{8}{7}\)
Y - 1/2 - 1/6 - 1/12 - 1/20 - 1/30 - 1/42 = 1
Đặt A= - 1/2 - 1/6 - 1/12 - 1/20 - 1/30 - 1/42
\(A=-\left(\frac{1}{2}+\frac{1}{6}+\frac{1}{12}+...+\frac{1}{42}\right)\)
\(A=-\left(\frac{1}{1.2}+\frac{1}{2.3}+...+\frac{1}{6.7}\right)\)
\(A=-\left(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+...+\frac{1}{6}-\frac{1}{7}\right)\)
\(A=-\left(1-\frac{1}{7}\right)\)
\(A=-\frac{6}{7}\).Thay A vào ta có \(Y-\frac{6}{7}=1\Leftrightarrow y=\frac{13}{7}\)
1/2 + 1/6 + 1/12 + 1/20 + 1/30 1/x = 41/42
5/6 + 1/x = 41/42
1/x = 41/42 - 5/6
1/x = 1/7
vậy x = 7
x + 1/2 + 1/6 + 1/12 + 1/20 + 1/30 + 1/42 = 1
x + 1/1*2 + 1/2*3 + 1/3*4 + 1/4*5 + 1/5*6 + 1/6*7 = 1
x + 1/1 - 1/2 + 1/2 - 1/3 + 1/3 - 1/4 + 1/4 - 1/5 + 1/5 - 1/6 + 1/6 - 1/7 = 1
x + 1/1 - 1/7 = 1
x + 6/7 = 1
x = 1 - 6/7
x = 1/7
x + 1/2 + 1/6 + 1/20 + 1/30 + 1/42 = 1
x + 65/84 = 1
x = 1 - 65/84
x = 19/84
em lớp 6 nha
B= 1/2 + 1/6 + 1/12 +1/20 + 1/30 + 1/42 + 1/56 + 1/72
B= 1/1*2 + 1/2*3 + 1/3*4 + 1/4*5 + 1/5*6 + 1/6*7 + 1/7*8 + 1/8*9
B=1-1/2+1/2-1/3+1/3-1/4+1/4-1/5+1/5-1/6+1/6-1/7+1/7-1/8+1/8-1/9
B=1+0-0-0-0-0-0-0-1/9
B=1-1/9
B=8/9
k em nha
A = 1/2 + 1/6 + 1/12 + 1/20 + 1/30 + 1/42 + 1/56
A = 1/1.2 + 1/2.3 + 1/3.4 + 1/4.5 + 1/5.6 + 1/6.7 + 1/7.8
A = 1/1 - 1/2 + 1/2 - 1/3 + 1/3 - 1/4 + 1/4 - 1/5 + 1/5 - 1/6 + 1/6 - 1/7 + 1/7 - 1/8
A = 1 + ( -1/2 + 1/2 ) + ( -1/3 + 1/3 ) + ( -1/4 + 1/4 ) + ( -1/5 + 1/5 ) + ( -1/6 + 1/6 ) + ( -1/7 + 1/7 ) - 1/8
A = 1 + 0 + 0 + 0 + 0 + 0 + 0 - 1/8
A = 1 - 1/8
A = 7/8
* Sửa đề tí nhé
B = 3/2 - 5/6 + 7/12 - 9/20 + 11/30 - 13/42 + 15/56
B = 3/1.2 - 5/2.3 + 7/3.4 - 9/4.5 + 11/5.6 - 13/6.7 + 15/7.8
B = 3 - 3/2 - 5/2 - ( -5/3 ) + 7/3 - 7/4 - 9/4 - ( -9/5 ) + 11/5 - 11/6 - 13/6 - ( -13/7 ) + 15/7 - 15/8
B = 3 - 3/2 - 5/2 + 5/3 + 7/3 - 7/4 - 9/4 + 9/5 + 11/5 - 11/6 - 13/6 + 13/7 + 15/7 - 15/8
B = 3 + ( -3/2 - 5/2 ) + ( 5/3 + 7/3 ) + ( -7/4 - 9/4 ) + ( 9/5 + 11/5 ) + ( -11/6 - 13/6 ) + ( 13/7 + 15/7 ) - 15/8
B = 3 + -4 + 4 + -4 + 4 + -4 + 4 - 15/8
B = 3 + 0 + 0 + 0 - 15/8
B = 3 - 15/8
B = 9/8